A method for analyzing the effect of implementing an enterprise system based on the complexity of activities - Lee, Chijoo; Lee, Chiheyon; Lee, Eul-Bum (Journal of Civil Engineering and Management, 2018)
This paper presents a method for analyzing the effect of implementing an enterprise system (ES) in the construction industry during the ES introduction and planning stages. The effect is a reduction in employees’ work time. The proposed method is based on the 1) level of digitalized and automated activities, the 2) complexity of the activities, and the 3) complexity of the processes in the workflow. The method was applied at a construction company that has no enterprise resource planning (ERP), and the method’s accuracy was evaluated by information technology consultants who have performed planning, construction, and operation in relation to ERP. The result shows that the effect of management business was the largest; most of this effect was on data management and review. After users became familiar with ERP, the reduction in data input time increased. The analysis method takes less time and costs less than using surveys to measure the work time and satisfaction of ES users. It can also identify processes in which the effect increases or decreases, thereby guiding any modifications of the ES before it is introduced.